(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
There is information in the literature that parents of children with developmental disabilities are more likely to be at risk of mental health problems. In this study, the mental health of parents of children with developmental disabilities was compared with that of parents of children without developmental disabilities. The conducted research showed that parents of children with developmental disabilities are more likely to be diagnosed with depression or other mental disorders than parents of children without developmental disabilities. These changes were related to the parents’ age at birth, income, and outcomes of health services opportunities. Parents of children with developmental disabilities may need programs and services that support their mental health